Long read and single molecule DNA sequencing simplifies genome assembly and TAL effector gene analysis of Xanthomonas translucens - Peng, Z.; Hu, Y.; Xie, J. Z.; Potnis, N.; Akhunova, Alina; Jones, J.; Liu, Z. H.; White, Frank F.; Liu, Sanzhen (My University, 2016)
Background: The species Xanthomonas translucens encompasses a complex of bacterial strains that cause diseases and yield loss on grass species including important cereal crops. Three pathovars, X. translucens pv. undulosa, X. translucens pv. translucens and X. translucens pv. cerealis, have been described as pathogens of wheat, barley, and oats. However, no complete genome sequence for a strain of this complex is currently available. Results: A complete genome sequence of X. translucens pv. undulosa strain XT4699 was obtained by using PacBio long read, single molecule, real time (SMRT) DNA sequences and Illumina sequences. Draft genome sequences of nineteen additional X. translucens strains, which were collected from wheat or barley in different regions and at different times, were generated by Illumina sequencing. Phylogenetic relationships among different Xanthomonas strains indicates that X. translucens are members of a distinct clade from so-called group 2 xanthomonads and three pathovars of this species, undulosa, translucens and cerealis, represent distinct subclades in the group 1 clade. Knockout mutation of type III secretion system of XT4699 eliminated the ability to cause water-soaking symptoms on wheat and barley and resulted in a reduction in populations on wheat in comparison to the wild type strain. Sequence comparison of X. translucens strains revealed the genetic variation on type III effector repertories among different pathovars or within one pathovar. The full genome sequence of XT4699 reveals the presence of eight members of the Transcription-Activator Like (TAL) effector genes, which are phylogenetically distant from previous known TAL effector genes of group 2 xanthomonads. Microarray and qRT-PCR analyses revealed TAL effectorspecific wheat gene expression modulation. Conclusions: PacBio long read sequencing facilitates the assembly of Xanthomonas genomes and the multiple TAL effector genes, which are difficult to assemble from short read platforms. The complete genome sequence of X. translucens pv. undulosa strain XT4699 and draft genome sequences of nineteen additional X. translucens strains provides a resource for further genetic analyses of pathogenic diversity and host range of the X. translucens species complex. TAL effectors of XT4699 strain play roles in modulating wheat host gene expressions.
Citation: Peng, Z., Hu, Y., Xie, J. Z., Potnis, N., Akhunova, A., Jones, J., . . . Liu, S. Z. (2016). Long read and single molecule DNA sequencing simplifies genome assembly and TAL effector gene analysis of Xanthomonas translucens. Bmc Genomics, 17, 19. https://doi.org/10.1186/s12864-015-2348-9
Keywords: Bacterial Leaf Streak; X. Translucens; Pacbio; Tal Effectors; Disease-Susceptibility Gene; Campestris Pv-Translucens